IMPROVEMENT OF THE DESIGN OF THE SHUTTLE DRUM IN THE SEWING MACHINE - Vafayeva, Zamira; Matyakubova, Jumagul; Mansurova, Munisa (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Today, in the process of sewing gauze, the lack of the ability to untie the shuttle thread, to ensure its tension evenly, is considered a disadvantage of this shuttle tube design. our goal is to improve the new construction of the shuttle bobbin in the sewing machine.